Kepribadian Pendidik dalam Perspektif Sosiologi (IAI Sunan Giri Trenggalek, 2025)
This article aims to reveal that educators play a very important role in the world of education, both formal educators (teachers) and non-formal educators such as parents. Many teachers feel that working as a teacher is lowly and despicable compared to office work or working at a PT, for example. This may be because the view of teachers is still narrow. A view that is generally materialistic, only tends to worldliness. Such a view is a wrong view. Working as a teacher is a noble and noble job, both from the perspective of society and the state. The high or low culture of a society and state, largely depends on the education and teaching given by teachers.